Effect of modified atmosphere package on attributes of sweet bamboo shoots after harvest - Wang, Ling; Liu, Miyang; Luo, Zheng; Chen, Yulong; Qi, Yingwei; Ye, Mingqiang; Chen, Feiping; Dai, Fanwei (Frontiers in Plant Science, 2024)
Tender bamboo shoots undergo rapid senescence that influences their quality and commercial value after harvest. In this study, the tender sweet bamboo shoots (‘Wensun’) were packed by a passive modified atmosphere packaging (PMAP) to inhibit the senescence process, taking polyethylene package as control. The increase in CO2 and the decrease in O2 gas concentrations in the headspace atmosphere of the packages were remarkably retarded by PMAP treatments. The modified gas atmosphere packaging inhibited the changes in firmness, as well as the content of cellulose, total pectin, and lignin in the cell walls of bamboo shoots. The enzymatic activities of cellulase, pectinase, and polygalacturonase that act on cell wall polysaccharides, and phenylalanine ammonia lyase, cinnamyl alcohol dehydrogenase, peroxidase, and laccase regulating the lignin biosynthesis were modified by PMAP treatment different from control during storage. The expression levels of the lignin biosynthesis genes PePAL3/4, PeCAD, Pe4CL5, PeC4H, PeCCOAOMT, PeCOMT, cellulose synthase PeCESA1, and related transcription factors PeSND2, PeKNAT7, PeMYB20, PeMYB63, and PeMYB85 were clearly regulated. These results suggest that PMAP efficiently retards the changes in lignin and cell wall polysaccharides, thus delaying the senescence of tender sweet bamboo shoots during storage.